Investigating the impact of environmental noise, humidity and surface treatment on mosque acoustic performance in Makassar, Indonesia - Asniawaty, Kusno; Nazli, Che Din; Abdul Wafi, Razali; Baharuddin, Hamzah; Nurul, Jamala; Rosady, Mulyadi; Edward, Syarif; Kusno, Kamil (Faculty of Education, Universiti Malaya, 2025)
Mosques serve as significant social venues where acoustic quality is paramount for enhancing speech intelligibility during prayers, sermons, and recitations. In contrast to performing venues, mosque acoustics necessitate a precise balance between reverberation for spiritual ambience and clarity for effective speech. However, in mosque architecture, acoustic considerations tend to be overlooked in the initial phases of architectural development. This study seeks to examine the impact of environmental noise, relative humidity, and surface treatments on the acoustic performance of two mosques in Makassar, Indonesia, namely the Mosque A and the Mosque B. The measurement of background noise levels (BN), reverberation time (RT), speech transmission index (STI), and sound pressure level (SPL) distribution was conducted through field measurement. The influence of different relative humidity levels and several surface treatment designs on essential parameters was conducted through acoustic simulation using ODEON room acoustic software. The findings indicated that both mosques displayed elevated background noise levels, primarily resulting from mechanical ventilation systems and traffic on nearby main roads. In both instances, RT measures are beyond recognised acoustic standards, suggesting acoustic conditions that could jeopardise speech intelligibility and comfort. Simulation analyses indicated that relative humidity profoundly affected RT, especially in the higher frequency ranges,while showing little effect on the STI and SPL distribution. The simultaneous use of wall and ceiling absorptive materials yielded the most substantial enhancements in acoustic performance, highlighting the significance of an integrated materials approachin mosque design.